Protective Role of Caffeic Acid in Cognitive Dysfunction and Oxidative Stress Induced by Colchicine in Rats - Raviteja, Surubhotla; Manandhar, Suman; Priya, Keerthi; Hari, Gangadhar; Pai, K Sreedhara Ranganath (Indian Journal of Pharmaceutical Education and Research, 2021)
Purpose: Alzheimer’s is a disease affecting mostly the Older population leading to the deterioration of cognitive capabilities. The protective effect of Caffeic acid in Colchicine-induced dementia was evaluated in the current study. Materials and Methods: Colchicine was administered intracerebroventricularly (ICV) to the lateral ventricle of the brain (at the coordinates 0.8 mm posterior to bregma, 1.8 mm lateral to the sagittal suture, 3.6 mm below the cortical surface) using robotic stereotaxic apparatus that results in Alzheimer’s type sporadic dementia. Caffeic acid at the dose of 50 mg/kg p.o, was administered daily for 25 days starting four days before the colchicine injection and evaluated for its neuroprotective activity. The spatial memory of animals was evaluated using Morris water maze followed by biochemical estimations of acetylcholinesterase and antioxidant markers in the hippocampal and frontal cortex region of the brain. Results: Intracerebroventricular injection of colchicine in rat brain resulted in decreased cognitive abilities as evident in escape latency and average speed of the retention trial. Significant changes in the escape latency were noted in Caffeic acid-treated group. The level of acetylcholinesterase and antioxidant markers like glutathione, catalase, lipid peroxidation, superoxide dismutase were significantly changed in the hippocampal region of the rats but not in the frontal cortex region in the caffeic acid treatment groups. Conclusion: The current study provides evidence for the neuroprotective and antioxidative potential of caffeic acid in intracerebroventricularly injected Colchicine-induced sporadic model of AD.
Keywords: Colchicine; Caffeic acid; Alzheimer’s disease; Antioxidant; Neuroprotection; Cholinesterase